MANAJEMEN KONFLIK DALAM ORGANISASI PENDIDIKAN ISLAM: DIMENSI KONSEPTUAL, TEMUAN EMPIRIS DI MADRASAH, DAN STRATEGI TRANSFORMASI MENUJU KONFLIK FUNGSIONAL - Fatkhurrohman Fatkhurrohman; Atiqoh Atiqoh; Rasad Mulyadi; Zakaria Syafei; Eka Srimulyani; Rijal Firdaos (STKIP Pesisir Selatan, 2026)
Conflict is an unavoidable social phenomenon in organizations, including Islamic educational institutions, yet the integration of normative Islamic principles with contemporary conflict management theory remains limited, particularly when supported by field-level empirical evidence. This study aims to: (1) analyze the conceptual dimensions of conflict management within an Islamic epistemological framework; (2) identify conflict dynamics in pesantren, madrasah, and Islamic higher education institutions; (3) examine the impact of conflict on organizational effectiveness; and (4) formulate strategies for transforming dysfunctional conflict into functional outcomes grounded in the values of syura, ‘adl, and ukhuwah. A qualitative approach was employed, combining a systematic literature review of 47 scholarly sources with structured interviews of 15 teachers at a madrasah to triangulate conceptual findings with field realities. Data were analyzed using the Miles, Huberman, and Saldaña (2014) model of data reduction, display, and conclusion drawing. The results show that conflict develops through five sequential stages and is triggered by internal, external, and cultural factors; the interview findings confirm that miscommunication, role ambiguity, and resource constraints are dominant triggers, while deliberation (musyawarah), leadership justice, and brotherhood (ukhuwah) effectively transform conflict into renewed SOPs, policies, and stronger work solidarity